Werther at work: Intra-firm spillovers of suicides - Martin Halla; Bernhard Schmidpeter (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
Suicide is a leading cause of death worldwide and a critical public health concern. We examine the hypothesis of suicide contagion within the workplace, investigating whether exposure to a coworker's suicide increases an individual's suicide risk. Using high-quality administrative data from Austria and an event study approach, we compare approximately 150,000 workers exposed to a coworker's suicide with a matched group exposed to a "placebo suicide". We find a significant increase in suicide risk for exposed individuals, with a cumulative treatment effect of 0.04 percentage points (33.3 percent) over a 20-year post-event period. Exposed individuals who also die by suicide are more likely to use the same method as their deceased coworker, strongly suggesting a causal link. Two placebo tests bolster this interpretation: workers who left the firm before the suicide and those exposed to a coworker's fatal car accident do not show an elevated suicide risk. – – Selbstmord ist eine der führenden Todesursachen weltweit und ein dringendes Problem der öffentlichen Gesundheit. Wir untersuchen die Hypothese der Nachahmung von Suiziden am Arbeitsplatz und prüfen, ob die Konfrontation mit dem Suizid eines Kollegen das Suizidrisiko eines Individuums erhöht. Mithilfe administrativer Daten aus Österreich und eines Event-Study Ansatzes vergleichen wir ungefähr 150.000 Beschäftigte, die mit dem Suizid eines Kollegen konfrontiert wurden, mit einer vergleichbaren Gruppe, die einem "Placebo-Suizid" ausgesetzt war. Unsere Ergebnisse zeigen einen signifikanten Anstieg des Suizidrisikos für betroffene Individuen, mit einem kumulierten Effekt von 0,04 Prozentpunkten (33,3 Prozent) über einen Zeitraum von 20 Jahren nach dem Ereignis. Betroffene Individuen, die ebenfalls durch Suizid sterben, neigen eher dazu, die gleiche Methode wie ihr verstorbener Kollege zu verwenden, was auf einen kausalen Zusammenhang hindeutet. Zwei Placebo-Tests stützen diese Interpretation: Arbeitnehmer, die das Unternehmen vor dem Suizid verlassen haben, und solche, die einem tödlichen Autounfall eines Kollegen ausgesetzt waren, zeigen kein erhöhtes Suizidrisiko.
Keywords: I10; I12; I18; D81; J10; 330; Suicide; workplace; contagion hypothesis; Werther-effect; mental health